Prevalence of Thyroid Hormone Dysfunction in Patients with Hyperlipidemia; A Hospital-Based Study - Sapkota, Subash; Paudel, Navaraj; Kafle, Ramchandra; Tiwari, Ashok; Acharya, Chandra Prasad; Bastola, Sanjib; Acharya, Ramesh Raj (Journal of National Heart and Lung Society Nepal, 2024)
Background: Hyperlipidemia is a well-established risk factor for cardiovascular disease and may be secondary to underlying conditions such as thyroid dysfunction. Thyroid hormones influence lipid metabolism by regulating LDL receptor activity, cholesterol synthesis, and triglyceride clearance. Current guidelines recommend thyroid function screening in patients with newly diagnosed hyperlipidemia. Methods: This hospital-based observational descriptive study was conducted at Manipal Teaching Hospital, Pokhara, Nepal. A total of 200 patients aged ≥15 years with hyperlipidemia, not on lipid-lowering therapy were enrolled. Fasting lipid profile and thyroid function tests (free T3, free T4, TSH) were measured. Associations between lipid parameters [triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), non-high-density lipoprotein cholesterol (non-HDL-C)] and thyroid status were analyzed using Pearson’s Chi-square test, with p-value<0.05 considered significant. Results: Among 200 patients, thyroid dysfunction was detected in both subclinical and overt forms. TC and non-HDL-C showed significant associations with thyroid dysfunction (p-value=0.016, φ=0.332; p-value=0.003, φ=0.428, respectively), with non-HDL-C showing the strongest correlation. TG showed a trend toward association (p-value=0.073), with overt hypothyroidism more frequent in the very high TG group (>500 mg/dL). LDL-C was not significantly associated with thyroid status (p-value=0.112). Conclusion: Thyroid hormone dysfunction, particularly subclinical and overt hypothyroidism, is common among hyperlipidemic patients and is significantly associated with elevated TC and non-HDL-C levels. Routine thyroid function screening in newly diagnosed hyperlipidemia may facilitate early detection and management, potentially improving lipid profiles and reducing cardiovascular risk.